Effects of Exposure to Low Zearalenone Concentrations Close to the EU Recommended Value on Weaned Piglets’ Colon - Iulian Alexandru Grosu; Cristina Valeria Bulgaru; Gina Cecilia Pistol; Ana Cismileanu; Daniela Eliza Marin; Ionelia Taranu (Toxins, 2023)
Pigs are the most sensitive animal to zearalenone (ZEN) contamination, especially after weaning, with acute deleterious effects on different health parameters. Although recommendations not to exceed 100 µg/kg in piglets feed exists (2006/576/EC), there are no clear regulations concerning the maximum limit in feed for piglets, which means that more investigations are necessary to establish a guidance value. Due to these reasons, the present study aims to investigate if ZEN, at a concentration lower than the EC recommendation for piglets, might affect the microbiota or induce changes in SCFA synthesis and can trigger modifications of nutritional, physiological, and immunological markers in the colon (intestinal integrity through junction protein analysis and local immunity through IgA production). Consequently, the effect of two concentrations of zearalenone were tested, one below the limit recommended by the EC (75 µg/kg) and a higher one (290 µg/kg) for comparison reasons. Although exposure to contaminated feed with 75 µg ZEN/kg feed did not significantly affect the observed parameters, the 290 µg/kg feed altered several microbiota population abundances and the secretory IgA levels. The obtained results contribute to a better understanding of the adverse effects that ZEN can have in the colon of young pigs in a dose-dependent manner.